O valor econômico do cultural: o caso da Fábrica Rheingantz na cidade do Rio Grande - RS - Silva, Rogério Piva da (2012)
Rheingantz Factory, founded in 1873 in Rio Grande, was a pioneer in industrialization in Rio Grande do Sul. The complex, which through the factory production helped to boost the local economy, is abandoned since the activity began to decline in the late 1960s. As a consequence, it starts to house unemployed and be vandalized. The neglect and degradation that has been suffering, shows that if nothing is done quickly, you can lose the only place industrial city of Rio Grande do Sul, which still retains some of its structure built. In order to provide a distinctive dimension to the agents and asset managers in making decisions, this study aims to measure the value assigned by society to the factory Rheingantz. For this, it will be used the contingent valuation method based on Pearce, Paglioli, among others. The economic valuation is justified by the need to make choices between what is essential to preserve and what is not, because of scarce resources. To this end, this study was conducted by the method of deductive approach, descriptive and field research. We interviewed 500 individuals of whom 87% believed that the plant represents a local identity, 84% should be overthrown as cultural heritage of the Rio Grande and 63% said they are willing to pay / donate for the preservation / conservation of cultural heritage represented by the Rheingantz, resulting in an average willingness to pay R$ 18.96 and total economic value of R$ 5,682,600.00